2012
DOI: 10.1128/aem.02062-12
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Glycol Metabolism by Pseudomonas putida

Abstract: dIn this study, we investigated the metabolism of ethylene glycol in the Pseudomonas putida strains KT2440 and JM37 by employing growth and bioconversion experiments, directed mutagenesis, and proteome analysis. We found that strain JM37 grew rapidly with ethylene glycol as a sole source of carbon and energy, while strain KT2440 did not grow within 2 days of incubation under the same conditions. However, bioconversion experiments revealed metabolism of ethylene glycol by both strains, with the temporal accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 41 publications
0
83
0
Order By: Relevance
“…D) suggests that the rate of ethylene glycol uptake or glycolate export from the periplasm is not affected, thus pointing to a possible transport effect on the aldehyde intermediates. That said, pedE and pedI are very highly expressed in both strains, and it is known that they are involved in the oxidation of a variety of alcohols and aldehydes including ethylene glycol (Arias et al ., ; Mückschel et al ., ). The essentiality of the Ped cluster was confirmed by the deletion of the pedE‐pedI cluster (PP_2673‐PP_2780) in the E6 strains, which eliminated their ability to grow on ethylene glycol (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…D) suggests that the rate of ethylene glycol uptake or glycolate export from the periplasm is not affected, thus pointing to a possible transport effect on the aldehyde intermediates. That said, pedE and pedI are very highly expressed in both strains, and it is known that they are involved in the oxidation of a variety of alcohols and aldehydes including ethylene glycol (Arias et al ., ; Mückschel et al ., ). The essentiality of the Ped cluster was confirmed by the deletion of the pedE‐pedI cluster (PP_2673‐PP_2780) in the E6 strains, which eliminated their ability to grow on ethylene glycol (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Analytes were eluted using a 300 × 8 mm organic acid resin column together with a 40 × 8 mm organic acid resin precolumn (both from CS Chromatographie, Langerwehe, Germany) with 5 mM H 2 SO 4 as mobile phase at a flow rate of 0.7 ml min −1 at 70°C. (Mückschel et al ., ) A list with retention times and detection limits is shown in the Supporting Information Table S4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Asiatic clams as well as the fungus Tricholoma matsutake were reported to produce ethylene glycol (30,31), and it is also known to be a product of ethylene metabolism in a number of higher plants (32). Whereas many aerobic bacteria utilize ethylene glycol by oxidation to glycolaldehyde and glycolate followed by an oxidase reaction to glyoxylate (33)(34)(35)(36), anaerobic bacteria use the alternative route via the acetaldehyde resulting from ethylene glycol dehydration catalyzed by the very oxygen-sensitive diol dehydratase (13,28,29). As recently shown, growth on 1,2-PD leads to the formation of bacterial microcompartments in the cytoplasm of Acetonema longum and A. woodii cells (15,37).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that this enzyme is associated with the glycolate utilization trait in E. coli (Pellicer et al ., ). However, P. putida KT2440 could not use glycolate as the sole carbon source for growth (Mückschel et al ., ), leaving the function of this enzyme uncertain. Growth on and utilization of d ‐lactate in minimal medium was fully abolished only when both Fe‐S d ‐iLDH and glycolate oxidase were absent.…”
Section: Discussionmentioning
confidence: 99%